Comparative Transcriptomic Analysis Reveals the Regulated Expression Profiles in Oreochromis niloticus in Response to Coinfection of Streptococcus agalactiae and Streptococcus iniae - Cui, Miao; Wang, Zibin; Yang, Yongchun; Liu, Ru; Wu, Min; Li, Yujie; Zhang, Qizhong; Xu, Delin (Frontiers in Genetics, 2022)
Tilapia (Oreochromis sp.) is one of the main valuable economical fishes in the world. Streptococcosis is commonly found in tilapia, causing severe and devastating effects in tilapia cultures. Streptococcus agalactiae and Streptococcus iniae are the main pathogens leading to tilapia streptococcosis. To understand the molecular mechanisms underlying differential streptococcal infection patterns, Nile Tilapias (Oreochromis niloticus) were infected by 1×107 CFU/mL S. agalactiae, 1×107 CFU/mL S. iniae and 1×107 CFU/mL S. agalactiae and S. iniae (1:1) respectively, and transcriptome analysis was conducted to the intestine samples of Nile Tilapia (Oreochromis niloticus) at 6 h, 12 h, 24 h and 7 d post-infection. A total of 6185 genes that differentially expressed among groups were identified. Eight differentially expressed genes (DEGs) including E3 ubiquitin-protein ligase TRIM39-like, C-X-C motif chemokine 10-like(CXCL 10), C-C motif chemokine 19-like, interleukin-1 beta-like, IgM heavy chain VH region, partial, IgG Fc-binding protein, proteasome subunit beta type-8 (PSMB8) and ATP synthase F(0) complex subunit B1, mitochondrial that involved in immune system were selected, and their expression levels in the coinfection group were significantly higher than those in either of the single infection groups. These genes were associated with 4 different KEGG pathways. Additionally, the differential expression of 8 DEGs was validated by RT-qPCR approach and their immunological importance was discussed. The results provided insight into the responses of tilapia against S. agalactiae and S. iniae at the transcriptome level, promoting our better understanding of immune responses for aquatic animal against Streptococcus.